London has fallen [videorecording (DVD)] - Butler, Gerard, 1969-; Eckhart, Aaron; Freeman, Morgan (Universal Pictures Home Entertainment : Universal Studios, 2016)
After the British Prime Minister passes away under mysterious circumstances, his funeral is a must-attend event for leaders of the western world. However, what starts out as the most protected event on Earth turns into a deadly plot to kill the world's most powerful leaders, and unleash a terrifying vision of the future. Only three people have any hope of stopping it: the President of the United States, his formidable Secret Service head, and an English MI-6 agent who rightly trusts no one.